PENGARUH HUBUNGAN SOSIALSISASI PENDIDIKAN SEKSUAL KOMPREHENSIF OLEH INFLUENCER MEDIA SOSIAL TERHADAP TINGKAT KESADARAN GENERASI Z MENGENAI ISU PENCEGAHAN KEKERASAN SEKSUAL - Ajeng Ratna Komala, - (2021)
Abstract Cases of sexual violence become exposures to the development of today's society that must receive special attention, because the cases can increas exponentially. In fact, this issue is still found today. In addition, it cam be found that the contribution to cases of sexual violencer in Indonesia are currently in their praductitve age anda on of the is the people in Z generation. Various formas of effoerts are made so that people can avoid sexual violence and on of them is by socialixing comprehensive sexual education carried on bye social media influencer. However, socialization trough social media needs to be reviewed whether it has a good impact and influence on the level of public awereness regarding the prevention of sexual violence. So this research is examined using a quantitative approach with a moderation hierarchy method, wich is used to test the effect of the relationship using three models. Then generation Z in Bandung became the target of this research. Then it can be concluded that the relationship obtained by each variable partially can have an effect and ilustrates tha comprehensive sexual education and social media influencer can have a positive influence.However, if the relationship of comprehensive sexual education socialzation to the level of public awarwness regarding the prevention of sexual violence cannot be moderated by social media influencer. Therefore, this moderator varieble can only be a predictor or independen variabel.